Discretionary Authority of Government Officials After Law Number 11 of 2020 concerning Job Creation in the Perspective of Government Administration: (Case Study of Constitutional Court Decision Number 91/PUU-XVIII/2020): Kewenangan Diskresi Pejabat Pemerintah Pasca Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja Dalam Perspektif Administrasi Pemerintahan: Studi Kasus Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 - Samuel Ivander Aritonang; Anna Erliyana (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
Discretion is a necessity for official governemt to execute public administration. The government will scarcely operate and may cause public service disfunction without a discretionary authority. The discretionary rules is stipulated in Law Number 30 year 2014 concerining The Administration of Government. This Law regulates that discretionary authority have limitations, i.e. prohibition to have any breach to the laws, in order to avoid arbitrariness by the official governemnt. However, Law Number 11 year 2020 concerning Job Creation has annulled such prohibition. The purpose of this research is to review discretionary authority according to Job Creation Law including the implementation the decision of Constitutional Court number 91/PUU-XVIII/2020. The method used herein is normative research which resulted that the execution of discretionary authority by the government upon the issuance of Constitutional Court’s decision have breached the laws and its legal system. The Government did not execute the Constitunal Court’s decision by issuing delegated legislations as well as emergency regulation on Job Creation.